Awareness and correlates of short‐term and long‐term consequences of alcohol use among Australian drinkers - Kerri Coomber; Richelle Mayshak; Ashlee Curtis; Peter G. Miller (Elsevier, 2017)
Abstract Objective: To investigate awareness of short‐term and long‐term consequences of alcohol use among a sample of Australian adult drinkers. Demographic correlates of the awareness of each consequence were also explored. Methods: Participants aged 18-45 years (n=1,061; mean age=33.2 years) drawn from an online panel completed a web‐based survey assessing demographics, awareness of alcohol warning labels, and awareness of seven short‐term and 12 long‐term consequences of alcohol use. Results: The level of awareness of short‐ and long‐term consequences ranged from 16% (breast cancer) to 69% (low coordination and slower reflexes). The study found consistent differences in awareness of consequences by gender, with some differences for specific consequences by age, education, SES, rurality and awareness of alcohol warning labels. Conclusions: Most consumers lack a sufficient understanding of the potential consequences of alcohol use. Particular subgroups of drinkers may not equate drinking with negative consequences. Implications for public health: Front‐of‐label alcohol warnings on all products and public health and education campaigns presenting messages targeting subgroups of drinkers could increase awareness of short‐ and long‐term negative health and social effects of alcohol use.